(untitled) (Journal of the College of Basic Education, 2026)
The aim of this research is to identify the impact of an artificial intelligence-based application on the achievement and visual thinking of second-grade middle school students in biology. The research was conducted in Baghdad. The research community consisted of second-grade intermediate female students within the Baghdad-Rusafa Second Education Directorate for the academic year 2024-2025. The research sample consisted of (68) female students distributed into two experimental groups, which included (33) female students who studied using an application based on artificial intelligence, and a control group, which included (35) female students who studied using the prevailing traditional method. Equivalence was achieved between the two research groups in the variables (previous achievement, chronological age, intelligence). The researcher prepared two tools: the achievement test, consisting of (40) paragraphs, and the visual thinking test, consisting of (30) paragraphs. The validity and reliability of the two tools were verified, and all psychometric properties were found. After applying the experiment, which lasted for (9) weeks, The two tools were applied to the basic research sample and the data were processed using appropriate statistical methods. The result showed the superiority of the experimental group students in the achievement and visual thinking variables. The researcher presented a number of proposals and recommendations, including the following: Integrating artificial intelligence applications into the teaching of science subjects, particularly the Classpoint AI application in teaching biology at the intermediate level. Raising awareness of artificial intelligence applications in education and their importance. The Ministry of Education should include visual thinking skills in curricula and textbooks and encourage teachers to employ them in their teaching.